Addressing China’s Growing Water Shortages and Associated Social and Environmental Consequences - Shalizi, Zmarak (World Bank, Washington, DC, 2012)
China has experienced a wide-scale and rapid transformation from an agricultural based economy to the manufacturing workshop of the world. The associated relocation of the population from relatively low density rural areas to very high density urban areas is having a significant impact on the quantity and quality of water available as inputs into the production and consumption process, as well as the ability of the water system to absorb and neutralize the waste byproducts deposited into it. Water shortages are most severe in the north of the country, where surface water diversion is excessive and groundwater is being depleted. In addition, the quality of water is deteriorating because of pollution, thereby aggravating existing water shortages. The biggest challenge ahead will be for national and local governments to craft policies and rules within China's complex cultural and legal administrative system that provide incentives for users to increase efficiency of water use, and for polluters to clean up the water they use and return clean water to stream flows. Using a standard public economics framework, water requirements for public goods-such as ecosystem needs-should be set aside first, before allocating property rights in water (to enable water markets to function and generate efficient allocation signals). Even then, water markets will have to be regulated to ensure public goods, such as public health, are not compromised. Until water markets are implemented, staying the course on increasing water and wastewater prices administratively and encouraging water conservation are necessary to reduce the wasting of current scarce water resources, as well as the new water supplies to be provided in the future.